WESTERN STUDY PARADIGM OF THE QUR'AN IN THE STUDY PROGRAM OF QUR'AN SCIENCE and TAFSIR STATE ISLAMIC UNIVERSITY OF MATARAM - rahman, Fazlur; Mutma’innah (el-Umdah, 2023)
One of the characteristics of Islam as a religion is openness, therefore in its history Muslims have interacted well with all communities so that it has become a factor of its famous progress. Open interaction is seen in the history of many of its characters who studied in the west without knowing the dichotomy of science. But lately, especially in the 20th and 21st centuries, the paradigm has begun to fade, replaced by skepticism, less acceptance of plurality of perspectives, such as Western scientific studies on the Qur'an, which as the locus of its reflection on the Qur'anic science student community and more specifically in the study program of Qur'anic Science and Tafsir Faculty of Ushuluddin and Religious Studies so that the portrait of the paradigm will look more verbal.